Effects of corticosteroids in patients with sickle cell disease and acute complications: a systematic review and meta-analysis - Lopinto, Julien; Gendreau, Segolene; Berti, Enora; Bartolucci, Pablo; Habibi, Anoosha; Dessap, Armand Mekontso (Haematologica, 2022)
Whether corticosteroids improve outcome in patients with acute complications of sickle cell disease (SCD) is still debated. We performed a systematic review of the literature with the aim of estimating effects of corticosteroids on the clinical course of vaso-occlusive crisis (VOC) or acute chest syndrome (ACS) in patients with SCD. The primary outcome was transfusion requirement during hospitalization. Studies were identified by search of MEDLINE and CENTRAL database. Three randomized clinical trials (RCT) and three retrospective cohort studies (RCS) were included, involving 3,304 participants and 5,562 VOC or ACS episodes. There was no difference between corticosteroids and standard treatment regarding transfusion requirement overall (odds ratio [OR]=0.98, 95% confidence interval [CI]: 0.38-2.53) but there was a significant interaction of the study type (P<0.0001): corticosteroid therapy was associated with a lower risk of transfusion in RCT (OR=0.13, 95% CI: 0.04-0.45) and a higher risk of transfusion in RCS (OR=2.12, 95% CI: 1.33-3.40. In RCT, the length of hospital stay was lower with corticosteroids as compared with standard treatment: mean difference - 24 hours (95% CI: -35 to -14). Corticosteroids were associated with an increased risk of hospital readmission as compared with standard treatment, in RCT, RCS, and the entire cohort: OR=5.91, 95% CI: 1.40-24.83; OR=3.28, 95% CI: 1.46-7.36 and OR=3.21, 95% CI: 1.97-5.24, respectively. Corticosteroids were associated with reduced number of transfusions and length of stay in RCT but not in RCS, with more rehospitalizations overall. Additional RCT should be conducted while minimizing the risk of rehospitalizations.